Isoimperatorin alleviates fungal keratitis by regulating NF-κB pathway and macrophage immune response - Song, Shiqi; Xu, Huirong; Liu, Mengzhu; Xu, Qiang; Wang, Ling; Wang, Fenglei; Wan, Xiaomei; Sun, Xiaoyan; Che, Chengye (Frontiers in Immunology, 2026)
PurposeThe purpose of this research study was to investigate the impact of isoimperatorin on Aspergillus fumigatus (A. fumigatus) keratitis and elucidate its underlying mechanisms via the TLR4/MyD88/IKK/NF-κB signaling pathway.Materials and methodsThe targets of the active ingredient isoimperatorin were identified via network pharmacology. Key interactions between isoimperatorin and its predicted targets were validated using molecular docking. In vitro RAW264.7 macrophage cells of A. fumigatus keratitis, the effects of isoimperatorin on inflammatory signaling and cell apoptosis were assessed using western blotting, immunofluorescence, and flow cytometry. In vivo C57BL/6 mouse models of A. fumigatus keratitis, the effects of isoimperatorin on inflammatory signaling, neutrophil infiltration, macrophage polarization, and cell apoptosis were assessed using quantitative real-time polymerase chain reaction (qRT-PCR), western blotting and immunofluorescence.ResultsIsoimperatorin inhibited TLR4/MyD88 complex formation and IKK/NF-κB phosphorylation, downregulated pro-inflammatory cytokines, reduced neutrophil infiltration, and promoted macrophage polarization from the M1 to the M2 phenotype. Additionally, it inhibited cell apoptosis and alleviated corneal epithelial damage.ConclusionThis study demonstrates that isoimperatorin exerts a protective effect against A. fumigatus keratitis primarily by modulating the host immune response. The mechanism is mediated through the multi-target inhibition of the TLR4/MyD88/IKK/NF-κB pathway, leading to a coordinated reduction in inflammation and tissue damage. These findings highlight the therapeutic potential of isoimperatorin as a novel immunomodulatory strategy for managing fungal keratitis.